434 Farmer's lung disease in a cohort of british agricultural workers. (24th April 2018) - Barber, Chris; Fishwick, David; Harding, Anne-Helen
Abstract : Introduction: Farmer's Lung Disease (FLD) is the oldest recognised form of occupational hypersensitivity pneumonitis (OHP) and remains one of the most commonly reported causes in Europe.The aim of this study was to provide novel data on the prevalence and demographic risk factors of FLD in a large cohort of British farm workers. Methods: Farmers were identified from the baseline survey of the PIPAH cohort (Prospective Investigation of Pesticide Applicators' Health). The demographics of workers, who self-reported a doctor diagnosis of FLD, were compared to the remainder of the cohort. Result: Questionnaire data was available for 5115 current or former farmers, representing a cumulative total of over 210, 000 years of farming practice. 26 farmers self-reported a diagnosis of FLD, representing a cohort prevalence of 5 per 1000. Those with FLD were all male, and were older, more likely to be involved in animal production and less likely to be involved in crop production only than those without FLD. Those with and without FLD did not differ in respect of years lived or worked on a farm, or their smoking status. Median age of FLD diagnosis was 35 (IQR 25–43, range 16–62), with a median latent period from first farm exposure of 28 years (IQR 20–42). Discussion: The prevalence of FLD in this British cohort (representing over 1% of British farmers) was in keeping with that reported from other countries. Age of diagnosis was very variable, with the majority of those affected having never smoked. Although most had worked on a mixture of farm types, workers with FLD were more likely to report only having lived on an animal versus cereal production farm